Keterlambatan Audit Berdasarkan Karakteristik Perusahaan dan Karakteristik Auditor - Hendi Hendi; Klesia Tamara (Faculty of Economics, Universitas Internasional Batam, 2017)
This study aims to determine the influence of company characteristic and auditor characteristic on audit delay on company listed in Indonesia Stock Exchange (IDX). Variables used in this study are profitability, leverage, audit complexity, firm size, audit committee, industry classification, number of subsidiaries, date of company financial closing, audit firm size, auditor opinion, and auditor change. The population of this research is a company listed in Indonesia Stock Exchange between year 2011 to 2015. Total research sample is 415 companies which selected by purposive sampling method over 5 years observation period. Data used in this research is from the financial statement of each public company (www.idx.co.id). Data obtained from the particular statement will be tested with regression panel. Program used in this research test is by SPSS (Statistical Package for the Social Sciences) version 22 and Eviews 8. The result had indicate that are profitability, leverage, audit complexity, firm size, audit committee, number of subsidiaries, and auditor opinion have significant impact on audit delay. And industry classification, date of company financial closing, audit firm size, and auditor change have no significant impact on audit delay.